Penerapan Bioengineering Penanaman Tanaman Penguat Lereng untuk Meningkatkan Ketahanan Bencana Longsor di Padukuhan Karangrejek - Abdul Kadir Jaelani; Yosi Marchita Kharisma Putri Wulandari; Cindy Kafka Navisa Dewi; Dwiana Margareta Lumbantoruan; Intan Pertiwi; Riam Rizki Zahira Satoto; Rizky Setyawan; Rochmana Dwi Rahayu; Sabrina Dwi Puspitasari; Wafiq Galindha Radyan (Universitas Muhammadiyah Manado, 2026)
Abstract: Padukuhan Karangrejek, Karangtengah, Imogiri, Bantul, is a sloping area prone to landslides due to high rainfall, soil erosion, and vegetation degradation. Landslides often threaten the safety of residents, damage infrastructure, and disrupt the sustainability of the local environment and economy. This study aims to apply bioengineering through the planting of slope-stabilizing plants to improve slope resistance to landslides using an environmentally friendly and sustainable nature-based approach. The methods included surveying planting locations, preparing planting holes, making tree marker boards, and participatory phased planting with the community. The types of plants used were Munggur, Soursop, Jackfruit, and Teak, which have strong root systems to strengthen soil structure and reduce erosion. The results showed an increase in soil cohesion through root penetration, a reduction in rainwater runoff, suppression of erosion, and a decrease in the risk of subsequent landslides. The positive impacts included increased soil water retention, improved soil fertility, community empowerment in disaster management, and economic added value from fruit and timber crops. Conclusion The application of bioengineering with Munggur, Soursop, Jackfruit, and Teak trees is an effective, inexpensive, and sustainable solution for landslide mitigation in Karangrejek Hamlet. Recommendations include monitoring growth periodically, expanding planting to other slopes, and integrating the program into the village's disaster resilience plan for long-term sustainability.